Farabi and the Modern World - Aydinli, Yasar (Eurasian Journal of Religious Studies, 2019)
The essay discusses the ethical and philosophical views of the great thinker and philosopher al-Farabi. The philosophical system created by al-Farabi deals with the main problems related to questions of God, the universe and man, as well as the place of man in the universe. The formation of philosophical thinking of al-Farabi was influenced by ancient Greek philosophy, in particular, the works of Aristotle. Al-Farabi created a whole encyclopedic system, where in his writings he considered such concepts as truth, logic and morality. In his philosophical reflections, al-Farabi touched on all aspects of human life. The importance of the work and the importance of the activities of Abu Nasr al-Farabi in the modern world is evidenced by the great attention paid to the study of his rich scientific heritage.
Keywords: Al-Farabi; ancient Greek philosophy; Aristotle; philosophical system; God; man; happiness